The role of shared intentions in the emergence of service ecosystems - Taillard, Marie; Peters, Linda D.; Pels, Jaqueline; Mele, Cristina (Elsevier, 2016)
With the increased prevalence of ecosystems across sectors, understanding what conditions enable their formation is important for both researchers and managers. Service-dominant logic (S-D logic) focuses on service ecosystems, in which actors are interdependent, and characterizes them as layered and nested within three levels (micro, meso, and macro). To understand their formation, this study draws from work in philosophy and the social sciences to introduce the concept of shared intentionality, an aspect of collective agency whose specific conditions result from and foster interdependence among actors, and to acknowledge the mediating role of the meso level in emergence. With these concepts, this study addresses a research question on how service ecosystems are formed and what role individual and collective agency play in this process. This study contributes to S-D logic research by offering a new understanding of service ecosystem formation as a process of emergence in which the development of shared intentions enables collective agency. To synthesize the contribution, this study uses a case to illustrate a conceptual framework in which the sharing of intentions among interdependent actors drives service ecosystem emergence step-by-step across distinct dynamic levels.